Implementing Mobile Public Services in Archipelagic Contexts: An Archipelagic Implementation Framework from Raja Ampat, Indonesia - Genova Furu; Dian Ferriswara; Sarwani Sarwani (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This research examines the implementation of mobile public services in archipelagic contexts, where dispersed settlements, dependence on sea transportation, weather uncertainty, and limited digital connectivity significantly constrain service access and continuity. Although digital government has developed rapidly, most previous studies focus on urban or mainland settings and rarely consider geography as a determining factor. This creates a gap in understanding how archipelagic conditions interact with governmental capacity, governance structures, and frontline practices. The study aims to explain the mechanisms of mobile service implementation under these constraints and to develop an Archipelagic Implementation Framework that integrates context, capacity, governance, and outcomes. Using a qualitative single-case study approach in Raja Ampat Regency, Indonesia, data were collected through in-depth interviews, policy documents, and limited observation, then analyzed using hybrid thematic analysis. The findings reveal that archipelagic constraints lead to frequent rescheduling, hybrid online–offline service delivery, increased coordination demands, and connectivity challenges. Service sustainability depends on staff rotation, portable infrastructure, and adaptive strategies by frontline actors. The proposed framework highlights how contextual constraints shape administrative capacity, coordination, and service outcomes, offering practical insights for resilient public service delivery.